2008
DOI: 10.1159/000148210
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Protein Thiols and Total Antioxidant Power in Pediatric Nephrotic Syndrome

Abstract: Background: Oxidative damage by free radicals has been implicated in kidney injury, especially in nephrotic syndrome (NS). Such a stress would influence the response of nephrotic children to therapy. Methods: The present study enrolled children with NS in active disease state and in remission and 50 healthy volunteers. Plasma protein thiol levels and ferric-reducing/antioxidant power were estimated spectrophotometrically in controls and in patients. Serum protein and albumin as well as urine protein were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 28 publications
(21 reference statements)
1
14
2
Order By: Relevance
“…In contrast, Karthikeyan et al [24] reported an increase in antioxidant status in children with NS. The native and total thiol and disulphide levels were significantly lower in the present study's NS patients.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In contrast, Karthikeyan et al [24] reported an increase in antioxidant status in children with NS. The native and total thiol and disulphide levels were significantly lower in the present study's NS patients.…”
Section: Discussionmentioning
confidence: 84%
“…Determination of the percentages of total thiols composed of native thiols is based on the native thiol/ total thiol ratio. Most of the literature on thiol and disulphide concerns low-molecular-weight thiol compounds and plasma total thiol [23,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, the majority were excluded after the first screening in terms of abstracts or titles, mainly because they were not relevant to INS. After full-text review of 14 articles, six [18][19][20][21][22][23] studies were excluded because they did not display the status of MDA, vitamin C or E. Finally, eight studies were included.…”
Section: Literature Searchmentioning
confidence: 99%
“…Levels of protein thiols and protein carbonyls in serum of brain tumor patients have been studied as an indicator of protein damage due to oxidative stress and significant alterations in their levels have been observed [22]. Many studies have observed altered protein thiols including alterations in the glutathione levels in various disease conditions with oxidative stress [23,24]. In this study, the salivary protein thiols were significantly decreased in the oral cancer patients when compared to healthy controls.…”
Section: Discussionmentioning
confidence: 55%